2005
DOI: 10.1080/10473289.2005.10464646
|View full text |Cite
|
Sign up to set email alerts
|

The Steubenville Comprehensive Air Monitoring Program (SCAMP): Analysis of Short-Term and Episodic Variations in PM2.5Concentrations Using Hourly Air Monitoring Data

Abstract: One-hour average ambient concentrations of particulate matter (PM) with an aerodynamic diameter Ͻ2.5 m (PM 2.5 ) were determined in Steubenville, OH, between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Ohio River Valley and possible urban regions beyond were found to be the significant sources of PM and its precursors in the Pittsburgh area and at other regional sites included in the study. 17 The Steubenville Comprehensive Air Monitoring Program Study noted that PM concentrations Ͼ35 g/m 3 were observed at a site in Steubenville, PA. 18 Based on the results from previous studies, continuous PM 2.5 mass concentration and speciation data were collected at the three monitoring sites located in Central and Southeast Ohio, and the data were used in a source apportionment assessment of regional and local sources using PSCF analysis and PCA in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Ohio River Valley and possible urban regions beyond were found to be the significant sources of PM and its precursors in the Pittsburgh area and at other regional sites included in the study. 17 The Steubenville Comprehensive Air Monitoring Program Study noted that PM concentrations Ͼ35 g/m 3 were observed at a site in Steubenville, PA. 18 Based on the results from previous studies, continuous PM 2.5 mass concentration and speciation data were collected at the three monitoring sites located in Central and Southeast Ohio, and the data were used in a source apportionment assessment of regional and local sources using PSCF analysis and PCA in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis will be studied in greater depth using hourly air monitoring data and upper air observations in a future paper. 35 Correlations among PM 2.5 , Gases, and Weather Conditions To further investigate and quantify the associations among PM 2.5 , gaseous co-pollutants, and meteorological conditions that were observed above, we used simple linear regression analyses. As discussed, adjusted values were used in these analyses to ensure that autocorrelation and seasonal patterns had been removed from each data set being considered.…”
Section: Episodes Of Elevated Pm 25 Concentrationmentioning
confidence: 99%
“…Although the results are not shown, Al and Zn fractional solubilities in autumn also correlated moderately to strongly (i.e., r s Ͼ 0.7) with concentrations of a number of other PM 2.5 chemical components, including EC and OC and several trace elements. These results are more suggestive of primary emissions of soluble forms of these metals, perhaps during inversion-driven pollution episodes that have been shown 30 to promote buildups in the concentrations of locally emitted pollutants during non-summer months in Steubenville, than of a photochemically driven mechanism of solubilization. Soluble Zn may have health implications; Fernandez et al 61 reported recently that exposure to ZnSO 4 aerosol led to a significant increase in lung permeability in mice, whereas exposure to ZnO aerosol did not induce such a response.…”
Section: Solubility Of Elements In Pm 25 At Steubenvillementioning
confidence: 92%
“…24,29,30 Figure 1 shows the locations of the five SCAMP outdoor ambient air monitoring sites. The central site in Steubenville was situated on the campus of Franciscan University of Steubenville (40.38 o N, 80.62 o W) atop a bluff overlooking the Ohio River, which flows from approximately due north to due south in the Steubenville vicinity.…”
Section: Methodsmentioning
confidence: 99%